Effects of Fluoxetine on Human Embryo Development - Kaihola, Helena; Yaldir, Fatma G.; Hreinsson, Julius; Hörnaeus, Katarina; Bergquist, Jonas; Olivier, Jocelien D. A.; Åkerud, Helena; Sundström-Poromaa, Inger (Frontiers in Cellular Neuroscience, 2016)
The use of antidepressant treatment during pregnancy is increasing, and selective serotonin reuptake inhibitors (SSRIs) are the most widely prescribed antidepressants in pregnant women. Serotonin plays a role in embryogenesis, and serotonin transporters are expressed in two-cell mouse embryos. Thus, the aim of the present study was to evaluate whether fluoxetine, one of the most prescribed SSRI antidepressant world-wide, exposure influences the timing of different embryo developmental stages, and furthermore, to analyze what protein, and protein networks, are affected by fluoxetine in the early embryo development. Human embryos (n = 48) were randomly assigned to treatment with 0.25 or 0.5 µM fluoxetine in culture medium. Embryo development was evaluated by time-lapse monitoring. The fluoxetine-induced human embryo proteome was analyzed by shotgun mass spectrometry. Protein secretion from fluoxetine-exposed human embryos was analyzed by use of high-multiplex immunoassay. The lower dose of fluoxetine had no influence on embryo development. A trend towards reduced time between thawing and start of cavitation was noted in embryos treated with 0.5 µM fluoxetine (p = 0.065). Protein analysis by shotgun mass spectrometry detected 45 proteins that were uniquely expressed in fluoxetine-treated embryos. These proteins are involved in cell growth, survival, proliferation, and inflammatory response. Culturing with 0.5 µM, but not 0.25 µM fluoxetine, caused a significant increase in urokinase-type plasminogen activator (uPA) in the culture medium. In conclusion, fluoxetine has marginal effects on the timing of developmental stages in embryos, but induces expression and secretion of several proteins in a manner that depends on dose. For these reasons, and in line with current guidelines, the lowest possible dose of SSRI should be used in pregnant women who need to continue treatment.